Sleepovers - Wilson J. Jacqueline (London, Corgi Books, 2007)
Amy, Bella, Chloe, Daisy and Emily are friends at school and have their own Alphabet Club. Daisy is the newest member and is desperate to fit in, even though Chloe is distinctly unfriendly to her at times. Throughout Daisy`s first year at the school, the girls plan ever-more elaborate sleepover parties for their birthdays.